Menekan Pernikahan Dini Melalui Dispensasi Nikah - Riyan Ramdani (VERITAS, 2023)
ABSTRACT Early marriage in Indonesia is an issue that needs attention, this can be seen, one of the ways, in the number of requests for marriage dispensation submitted to the court following the revision of the Marriage Law. In 2020 there were around 65,000 marriage dispensation cases and this will decrease in 2022 to 55,000 cases submitted. Even so, these numbers are still quite fantastic. This research uses a qualitative descriptive method with the type of library research. The results of this research, one way that can be attempted to reduce the rate of early marriage is through marriage dispensation, by creating a Best Interests Report for the Child which is included in the decision and used as material for the judge's consideration, with the hope that parents who consent can revoke their permission. Keywords: Marriage Dispensation, Marriage, early marriage.